A STUDY OF ERGONOMICS AND ITS EFFECT ON THE HOUSEKEEPING EMPLOYEES ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Ergonomics is the science of designing work as per the human body, it is used by the management to  make the work processes safe for their workers. Housekeeping involves lots of physical work, therefore it is necessary  that such research should be done on housekeeping department employees. Objectives: The objectives of this study  were: to understand the application of ergonomics in the housekeeping department, to study the effects and challenges  of ergonomics on the members of the housekeeping team, and to explore the awareness of ergonomics amongst the  housekeeping employees. Methodology: The research design was a combination of experimental & descriptive. 100  housekeepers from 4 & 5 star hotels in Delhi-NCR were participants of the work. A questionnaire consisting of close ended and few open-ended questions was circulated among the respondents on one to one basis. To study the fatigue  rate while working, oxygen and pulse rate of the respondents was also recorded. Data analysis was done on the basis of  gender. Results: The findings state that 98% of the housekeeping department employees were aware about the concept  of ergonomics and its application in housekeeping. Unfortunately, due to constraint of time and tight work schedule,  a housekeeper cannot always follow the practices of ergonomic. Oxygen level decreased (98.15±0.08) after doing the  task and the pulse rate increased (95.54±1.52) after completing their task. Conclusion: Housekeepers are exposed to a  range of ergonomic risk factors and are prone to posture related injuries. It has also been seen that there is a substantial  difference in level of energy lost when the housekeepers are working in a hurry.
Keywords: Ergonomics; Musculoskeletal Disorder (MSD); Hotel Industry; Health and Safety